SIFAT MEKANIK DARI BIOKOMPOSIT FILM PATI UBI KAYU DENGAN PENGUAT SERAT AKAR BUAH NAGA (HYLOCEREUS POLYRHIZUS) - Melbi Mahardika; Hairul Abral; Anwar Kasim; Syukri Arief; Mochamad Asrofi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Dragon fruit root fiber used as a reinforcement in the biocomposites film of cassava starch. The production method of biocomposites film was solution casting. The cassava starch serves as the matrix in the biocomposites film. The variation of amount fiber in matrix was 2, 4 and 6% from dry starch weight basis. Isolation of dragon fruit root fiber used alkalization and bleaching process with NaOH, NaClO2 and CH3COOH, respectively. Glycerol was used as plasticizers. Mechanical properties of biocomposites was determined by tensile test. The result shows that, tensile strength increased 200% after the addition of 6% fiber compared to pure starch film. Tensile test data was supported by X-Ray Difraction (XRD). Keywords: Biocomposite, Cassava Starch, Dragon fruit root fiber, Mechanical properties, XRD.